RDPLF 2022 annual report: Profile of home hemodialysis patients in Belgium and Francel (synthetic raw results) - Christian Verger; Emmanuel Fabre (Bulletin de la Dialyse à Domicile, 2023)
We present primary descriptive data in the form of tables and graphs for patients treated with home hemodialysis in France and French-speaking Belgium in 2022. These data were recorded in the database of the French-speaking Register of Peritoneal Dialysis and Home Hemodialysis (RDPLF).